Effect of dietary habits on laser fluorescence values of visually sound occlusal surfaces among Finnish schoolchildren - VUOKKO ANTTONEN (IAPD and Blackwell, 2008)
Dental caries is still a public health concern in Finland. The mean DMFT score among 12- year-old children was 1.2 in 1991 and has remained at that level 1 . During the past 15 years, sales of chocolate and candy have increased markedly 1 , while the frequency of toothbrushing and, hence, exposure to fluoridated toothpaste have remained among the lowest in Europe 2,3 . So far, attempts to identify in advance those individuals who are likely to develop dental decay have not been very successful 4 . Therefore, we decided to determine whether laser fluorescence could be used to detect dietary habits that favour the development of enamel demineralization.